Don Williams interviewed by John Meredith and Rob Willis in John Meredith folklore collection - Williams, Donald, 1902-; Meredith, John, 1920-2001.; Willis, Rob, 1944- (1993)
Folkloric recording. Don Williams sings country and western songs.
1. Conversation: biodata, how he had been a shearers' cook, how he later delivered the Sporting Globe newspaper by sidecar, his ambition to move up to a general postal carrier as well as a Country and Western singer -- 2. Riding down the trail -- 3. Freight train yodel -- 4. I'm just a happy-go-lucky cow hand -- 5. Young at heart -- 6. Mandrake -- 7. Texas Dan -- 8. Old rocking chair.
Recorded on June 2, 1993 at Batemans Bay, N.S.W.
Digital master available
Keywords: Williams, Donald, -- 1902- -- Interviews; Country music -- New South Wales; Singing; Folk singers -- New South Wales -- Batemans Bay -- Interviews